(untitled) (Global Journal of Management and Business Research, 2011)
Our study explores the influences of age and experience on stress and depression and the relationship between stress and depression among the women information technology (IT) professionals in Bangalore, Karnataka. The present study aimed at i) To find out the level of stress and depression experienced by women IT professionals ii) To understand the impact of age and experience on stress and Depression iii) to study the relationship between Stress and depression. iv) to know the factors causing of stress in software companies. The study was conducted in Bangalore , Karnataka with a sample of 250 women software professionals. The sample selection was done by convenience sampling method. The data was analyzed using descriptive one way analysis of variance and Pearson#x2019;s correlation test . Results showed that the women software professionals experienced moderate level of stress and stress dimension. This study reveals that 85 percent of the respondents experience medium level of depression and also suggested the age and experience significantly influence the over all stress and depression experienced by the employees. Our study shows that there might be a strong relationship between over all stress and depression.